2018
DOI: 10.3892/etm.2018.5778
|View full text |Cite
|
Sign up to set email alerts
|

Seminal bacterial composition in patients with obstructive and non‑obstructive azoospermia

Abstract: A number of culture-dependent and -independent studies have reported that the number and significance of bacterial species in semen may have been underestimated. The aim of the present study was to profile the seminal microbiome in patients with obstructive or non-obstructive azoospermia. A high-throughput sequencing method was adopted to sequence genomic DNA extracted from the semen of healthy people (C group), patients with obstructive azoospermia (OA group) and patients with non-obstructive azoospermia (NOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 32 publications
7
47
1
2
Order By: Relevance
“…There is growing evidence that microbes play an important role in human development, physiology, immunity, and nutrition (11) As one of the most important human-microbial habitats, the vaginal secretions and vaginal epithelial cells in vagina provide rich nutrients for the growth of a wide variety of pathogenic (e.g., Gardnerella and Prevotellas) and non-pathogenic (e.g., Lactobacillus) organisms (12,13), of which Lactobacilli can help host to prevent vaginal infection via producing lactic acid, hydrogen peroxide, bacteriocins (14).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that microbes play an important role in human development, physiology, immunity, and nutrition (11) As one of the most important human-microbial habitats, the vaginal secretions and vaginal epithelial cells in vagina provide rich nutrients for the growth of a wide variety of pathogenic (e.g., Gardnerella and Prevotellas) and non-pathogenic (e.g., Lactobacillus) organisms (12,13), of which Lactobacilli can help host to prevent vaginal infection via producing lactic acid, hydrogen peroxide, bacteriocins (14).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that intestinal microbes have an important role in human health (20,(29)(30)(31)(32). Therefore, after confirmation of the antioxidant effect of CA, the present study further investigated the potential effect of CA on common beneficial microbes and pathogens in the human microbiota.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, Hou et al, based on microbial communities clustering, were able to discriminate six different groups among healthy semen donors [21]. Chen et al, studying azoospermic patients, found a prevalence of the Lactobacillus genus [22], while another study by Monteiro et al, showed a low abundance of Lactobacilli [9]. Mandar et al, comparing the semen microbiome of patients with prostatitis versus controls, found a higher amount of Lactobacilli, and in particular L. iners, in the healthy subjects group [23].…”
Section: The Combined Multiple Composition Of Semen Microbiomementioning
confidence: 99%
“…Balmelli et al, by analyzing 3196 infertile men, identified a correlation between the presence of the Bacteroides ureolyticus and the increased presence of short-tailed spermatozoa [35]. More recently, next generation sequencing-based studies have been carried out to highlight microbial features in semen samples specifically related to infertility [8,9,21,22]. Hou et al did not find significant differences among controls and infertile men, but were able to identify a correlation between the presence of the Anaerococcus and a reduced sperm quality, suggesting that this bacterium may play a role in infertility [21].…”
Section: The Role Of Semen Microbiome On Reproductionmentioning
confidence: 99%
See 1 more Smart Citation